DEVELOPMENT OF PBL-TARL-BASED CIRCLE E-LKPD ON MIDDLE SCHOOL STUDENTS' PROBLEM-SOLVING ABILITIES - Hanif Roihan Fikri; Novaliyosi Novaliyosi; Maman Fathurrohman (Universitas Muhammadiyah Metro, 2026)
This Research and Development (R&D) study aims to develop and evaluate the feasibility of an interactive e-LKPD based on Problem-Based Learning (PBL) integrated with the Teaching at the Right Level (TaRL) approach. The novelty of this study lies in combining PBL and TaRL to accommodate students’ diverse cognitive abilities. The research involved 22 eighth-grade students of SMP Negeri 2 Menes and employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected using expert validation sheets, practicality questionnaires, and mathematical problem-solving tests on circle material. The results showed that the e-LKPD achieved a high level of validity, with an average expert validation score of 85%. The practicality level reached 90% based on teacher responses and 86.96% based on student responses, both categorized as very practical. Effectiveness testing using the N-Gain score showed an increase of 0.4412, which falls into the moderate category. In addition, the paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant improvement in students’ mathematical problem-solving skills after using the e-LKPD. In conclusion, the integration of PBL and TaRL in this e-LKPD is proven to be valid, practical, and effective. This study contributes by providing an adaptive learning medium aligned with students’ initial ability levels, which can be implemented by educators to enhance problem-solving skills at the junior high school level. Penelitian Research and Development (R&D) ini bertujuan untuk mengembangkan sekaligus menguji kelayakan e-LKPD interaktif berbasis Problem-Based Learning (PBL) yang diintegrasikan dengan pendekatan Teaching at the Right Level (TaRL). Kebaruan (novelty) penelitian ini terletak pada sinergi model PBL dan pendekatan TaRL yang dirancang secara spesifik guna memfasilitasi heterogenitas pemahaman kognitif siswa secara adaptif. Penelitian ini melibatkan sampel uji coba sebanyak 22 siswa kelas VIII di SMP Negeri 2 Menes. Proses pengembangan produk berlandaskan pada model instruksional ADDIE (Analysis, Design, Development, Implementation, Evaluation). Pengumpulan data dilakukan melalui instrumen lembar validasi ahli, angket kepraktisan, serta tes kemampuan pemecahan masalah matematis pada materi lingkaran. Hasil analisis data mengindikasikan bahwa e-LKPD memenuhi kriteria sangat valid dengan skor rata-rata validasi ahli materi dan media sebesar 85%. Tingkat kepraktisan produk berdasarkan respon guru dan siswa berturut-turut mencapai 90% dan 86,96% (kategori sangat praktis). Pengujian efektivitas melalui analisis N-Gain score menghasilkan peningkatan sebesar 0,4412 (kategori sedang). Lebih lanjut, uji paired sample t-test menunjukkan nilai signifikansi 0,000 (p < 0,05), yang mengonfirmasi adanya peningkatan kemampuan pemecahan masalah matematis secara signifikan pasca-penggunaan e-LKPD. Kesimpulannya, integrasi PBL dan TaRL dalam e-LKPD ini terbukti valid, praktis, dan efektif. Kontribusi utama dari penelitian ini adalah tersedianya alternatif media pembelajaran matematis yang adaptif terhadap tingkat kemampuan awal siswa, yang secara praktis dapat diimplementasikan oleh pendidik untuk mengoptimalkan kemampuan pemecahan masalah di tingkat sekolah menengah pertama.